2006
DOI: 10.1021/mp060001j
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Intravesical Drug/Gene Delivery

Abstract: Targeting of the drugs administered systemically relies on the higher affinity of ligands for specific receptors to obtain selectivity in drug response. However, achieving the same goal inside the bladder is much easier with an intelligent pharmaceutical approach that restricts drug effects by exploiting the pelvic anatomical architecture of the human body. This regional therapy involves placement of drugs directly into the bladder through a urethral catheter. It is obvious that drug administration by this rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
94
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 140 publications
0
94
0
3
Order By: Relevance
“…This layer is known to exhibit a tough barrier function that allows the instillation of potentially toxic drugs to achieve a localised pharmacological effect whilst avoiding systemic effects [19]. Diffusion of aminoglycosides across the uroepithelium is even more limited because of their polar cationic nature.…”
Section: Discussionmentioning
confidence: 99%
“…This layer is known to exhibit a tough barrier function that allows the instillation of potentially toxic drugs to achieve a localised pharmacological effect whilst avoiding systemic effects [19]. Diffusion of aminoglycosides across the uroepithelium is even more limited because of their polar cationic nature.…”
Section: Discussionmentioning
confidence: 99%
“…1 Besides the uroplakins-rigid plaques covering the round surfaces of apical cells-the mucin layer, which overlies the uroplakins and is composed of GAGs, further augments the strength of the permeability barrier, which acts by physically blocking instilled drug molecules from reaching the underlying tight junctions and cell membrane. 45 It is possible that the layers of uroplakins and mucin acted to prevent the absorbance of celecoxib, greatly reducing its therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high surface to volume ratio of the PEI nanoparticles may have also had a role in the transvesical absorption of encapsulated gene delivery complexes. 45 The destruction of GAG and uroplakin layers through electrocautery can be eliminated as reasons for successful gene delivery. Figure 4 demonstrates that unmodified PEI/DNA complexes can successfully transfect intact murine bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this drug has been explored increasingly more intensively and gradually more widely used. Current clinical studies have demonstrated that drugs with liposome as a carrier have advantages such as immunogenicity, insignificant toxicity and side effects, as well as easy adsorption (Tyagi et al, 2006). At present, doxorubicin, containing liposome as a drug carrier in the treatment of cancer, has been mainly divided into pegylated liposomal doxorubicin (PLD) and non-PLD (NPLD), the major difference being whether a polyethylene glycol-modified agent is contained or not.…”
Section: Introductionmentioning
confidence: 99%